2008
DOI: 10.1177/0959683608089658
|View full text |Cite
|
Sign up to set email alerts
|

Long-term stability of permafrost in subarctic peat plateaus, west-central Canada

Abstract: Long-term vegetation succession and permafrost dynamics in subarctic peat plateaus of west-central Canada have been studied through detailed plant macrofossil analysis and extensive AMS radiocarbon dating of two peat profiles. Peatland inception at these sites occurred around 5800–5100 yr BP (6600–5900 cal. BP) as a result of paludification of upland forests. At the northern peat plateau site, located in the continuous permafrost zone, palaeobotanical evidence suggests that permafrost was already present under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
47
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 33 publications
4
47
0
Order By: Relevance
“…Peatlands presently underlain by permafrost initiated mostly in permafrost-free environments, both in Canada (Zoltai & Tarnocai 1975;Sannel & Kuhry 2008) and in parts of the Russian Arctic (Oksanen et al 2001). In continental western Canada, basal peat ages range from 9000 to 3000 a BP, with the oldest dates in the Rocky Mountain foothills and northern Alberta, and the youngest dates in the southern Boreal Forest and Aspen Parkland (Halsey et al 1998).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Peatlands presently underlain by permafrost initiated mostly in permafrost-free environments, both in Canada (Zoltai & Tarnocai 1975;Sannel & Kuhry 2008) and in parts of the Russian Arctic (Oksanen et al 2001). In continental western Canada, basal peat ages range from 9000 to 3000 a BP, with the oldest dates in the Rocky Mountain foothills and northern Alberta, and the youngest dates in the southern Boreal Forest and Aspen Parkland (Halsey et al 1998).…”
mentioning
confidence: 99%
“…However, there also appears to be considerable variability in vegetation-permafrost interactions. Not all permafrost peat profiles show collapse-aggradation cycles (Sannel & Kuhry 2008), and alternative pathways to peat plateau formation have been proposed (Oksanen et al 2001). Not all instances of permafrost collapse can be linked to fire (Kuhry 2008), and not all fires trigger permafrost collapse (Sannel & Kuhry 2008).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Macrofossils of this species from the Late Tertiary have been found in non-glaciated regions of Alaska (Matthews and Ovenden 1990) and in northern and northeastern Siberia (Nikitin 2006), from the end of the Wisconsin interglacial in Nova Scotia (Mott et al 1982), and in the Early Würm in Siberia (Laukhin et al 2007). Other studies have reported only Early, Middle, or Late Holocene macrofossils from North America, Europe, and Asia (Bhiry and Filion 1996;Booth and Jackson 2003;Booth et al 2004;Sannel and Kuhry 2008;Novenko et al 2009). The pollen and macrofossil records of the other two taxa, L. b ssp.…”
Section: Identification Of Past Climatic Refugia and Future Macrorefugiamentioning
confidence: 99%